2014
DOI: 10.1186/ar4535
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, clinical and radiographic signs in knee osteoarthritis susceptibility

Abstract: IntroductionOsteoarthritis (OA) is considered to be a multifactorial and polygenic disease and diagnosis is mainly clinical and radiological. Correlation between radiographic data and clinical status has been reported. However, very few studies, especially in Caucasian people, describe the association between the Kellgren and Lawrence OA grading scale (KL) and genetic alterations to better understand OA etiopathogenesis and susceptibility. In order to update the knee OA grading, in this study we assessed the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
3
19
0
1
Order By: Relevance
“…Our results were also consistent with the results of the study conducted by Minafra et al (26) that indicated the presence of an association between the presence of the TT genotype and radiological severity of KOA represented by the K-L score (p=0.02).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results were also consistent with the results of the study conducted by Minafra et al (26) that indicated the presence of an association between the presence of the TT genotype and radiological severity of KOA represented by the K-L score (p=0.02).…”
Section: Discussionsupporting
confidence: 83%
“…The grading of OA is based on the radiological classification of the K-L score and is usually aided by other general or specific joint clinical and functional scores (26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the pathogenesis of OA is still unclear; however, it is widely accepted that genetics plays a main role in the prevalence and progression of this disease;4 even prediction tools for knee OA based on genetic and clinical information have been developed 5 6. Besides, during the last years, increasing evidence points to the implication of the mitochondria and the mitochondrial DNA (mtDNA) haplogroups in the pathogenesis of the disease 2 7 8…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of MATN-3 identified its anti-anabolic and pro-catabolic functions, suggesting that it plays an important role in OA (22,23 Two studies conducted by Vincourt et al (25,26) revealed higher levels of MATN-3 in both the serum and synovial fluid of OA patients.…”
Section: Discussionmentioning
confidence: 99%